TO EXAMINE LEADER-MEMBER EXCHANGE AS MODERATING VARIABLE ON THE INFLUENCE OF EMPLOYEE PSYCHOLOGICAL UNCERTAINTY TOWARD EMPLOYEES’ JOB SATISFACTION AND TURNOVER INTENTION - Muhammad Zakiy (Journal of Leadership in Organizations, 2019)
The studies revealed that organizational change could create employee’s psychological uncertainty. However, this study argues that the quality of leader-member exchange enables to control the impact of the psychological uncertainty during the change toward employee’s attitude. This study represents job satisfaction and turnover intention as proxy of employee’s attitude for that matter. Based on social exchange theory, quality relationship of leader and employees affects on the relationship of psychological uncertainty and employee’s job satisfaction and turnover intention. This study selected private hospitals experiencing the changes of operational system for complying with national health security system. This study conducted cross-section survey for individual level-analysis. This study produces some findings. Firstly, the LMX has been failed to reduce the negative influence of psychological uncertainty towards employee’s job satisfaction, although the quality of the LMX was good. employee’s job satisfaction is more perceived as  personal afective state experienced during the organizational change. Secondly, the LMX has been successfully moderated the positive influence of the psychological uncertainty towards employee’s turnover intention.The data were collected by using questioners, distributed to the employees who worked in hospitals in Yogyakarta Province. There were 193 questioners that could be collected and analyzed by using Moderated Regression Analysis (MRA) to test the hypothesis by using SPSS application version 21. The result of the study shows that psychological uncertainty had negative correlation to employee’s job satisfaction and positive influence to psychological uncertainty toward turnover intention. Besides, LMX was proven to moderate positive influence of psychological uncertainty toward turnover intention, but it could not moderate negative influence of psychological uncertainty toward job satisfaction.